Counterfeiting and fraud in supply chains - Soucie, Sanda; Peštek, Almir (Emerald Publishing Limited, 2022)
The manufacture and sale of counterfeit products is a widespread problem that affects a wide range of industries - from the pharmaceutical industry, electronics, and electrical equipment industry, clothing, footwear, to food, cosmetics, and luxury products industries. Counterfeiting and Fraud in Supply Chains explains the reasons behind the popularity of counterfeiting and fraud among both consumers and companies, a systematic and holistic overview and critical examination of the situations that have caused an increasing trend of those criminal activities. For all businesses, counterfeiting causes serious economic and social impact and can even be dangerous, posing health, privacy, and safety risks ranging from mild to life-threatening. Covering topics from the harmful effects of counterfeiting related to the environment, trade, foreign investment, employment, innovation, and criminality, Counterfeiting and Fraud in Supply Chains documents the unregulated production and the use of dangerous machinery and materials to attain a high profit margin. Counterfeiting and Fraud in Supply Chains boosts the existing knowledge about the profoundly multi-faceted dimension of the counterfeiting market, comprising the work of a team of theorists and practitioners who characterize a multidisciplinary approach to counterfeiting and fraud.